MAKNA ILUSTRASI SAMPUL MAJALAH TEMPO EDISI ‘KEJARLAH DAKU, KAU KUBEKAP’ - Ahdiyat, Azhar Natsir; Saidi, Acep Iwan; Sachari, Agus (KK Komunikasi Visual & Multimedia Fakultas Seni Rupa dan Desain Institut Teknologi Bandung, 2024)
Cases of corruption involving well-known figures in Indonesia always draw public attention. One such figure is the politician Setya Novanto, who was embroiled in the e-KTP corruption case in 2017. This case was considered a significant corruption case, thus the topic also expanded and became a concern for the society. Due to the importance of this case, Setya eventually became the main figure in the cover illustration of Tempo Magazine's edition titled